1980
DOI: 10.1029/rg018i001p00269
|View full text |Cite
|
Sign up to set email alerts
|

The heat flow through oceanic and continental crust and the heat loss of the Earth

Abstract: Simple thermal models based on the creation and cooling of the lithosphere can account for the observed subsidence of the ocean floor and the measured decreased in heat flow with age. In well‐sedimented areas, where there is little loss of heat due to hydrothermal circulation, the surface heat flow decays uniformly from values in excess of 6 µcal/cm² s (250 mW/m²), for crust younger than 4 Ma (4 m.y. B.P.), to close to 1.1 µcal/cm² s (46 mW/m²) through crust between 120 and 140 Ma. After 200 Ma the heat flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
498
3
3

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,140 publications
(529 citation statements)
references
References 158 publications
(113 reference statements)
25
498
3
3
Order By: Relevance
“…However, the largest of such potential compositional anomalies in the Pritzwalk area unfortunately is devoid of q s observations. Thus it cannot be verified by the present data whether a thick complex of mafic rock emplaced at mid-crustal level above a thick lower crust (Franke et al 1996;Kuder, 2002) The high average q s in the NEGB of 77 mW m -2 correlates with the heat flow of provinces younger than 250 Ma (Sclater et al, 1980;Sclater et al, 1981) and is in contrast to values from older, tectonically stable provinces (50 mW m -2 ). The range of q s in the NEGB is similar to observations made farther east, in the western part of PB ( In the NEGB models, an increase of crustal A on the expense of q m to accommodate the high q s seems unjustified.…”
Section: Discussioncontrasting
confidence: 49%
“…However, the largest of such potential compositional anomalies in the Pritzwalk area unfortunately is devoid of q s observations. Thus it cannot be verified by the present data whether a thick complex of mafic rock emplaced at mid-crustal level above a thick lower crust (Franke et al 1996;Kuder, 2002) The high average q s in the NEGB of 77 mW m -2 correlates with the heat flow of provinces younger than 250 Ma (Sclater et al, 1980;Sclater et al, 1981) and is in contrast to values from older, tectonically stable provinces (50 mW m -2 ). The range of q s in the NEGB is similar to observations made farther east, in the western part of PB ( In the NEGB models, an increase of crustal A on the expense of q m to accommodate the high q s seems unjustified.…”
Section: Discussioncontrasting
confidence: 49%
“…Ocean crust that is older than about 50-70 million years does not produce significant hydrothermal circulations [Stein et al, 1995], yet continued cooling and radiogenic decay maintain a background heat flux of 38-46 mW m -2 [Sclater et al, 1980]. What is perhaps most notable from a thermodynamic perspective is the division of heat flux into the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of this heat flux is absorbed into the abyssal oceans and marginal basins [Sclater et al, 1980]. Prior work has argued that both local hot spots (forming rising plumes) along the mid-ocean ridge axes [e.g., Stommel, 1982] and the more pervasive diffusive heating away from the ridge systems [e.g., Thompson and Johnson, 1996] play important roles in the abyssal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Oceanic heat flow can be explained by these models if hydrothermal activity at the ridge is taken into account (6); recently it has been demonstrated that the short wavelength change in geoid elevation over ridges predicted by these simple models is also readily observed (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%